Production of dragon fruit powder using spray drying method - Mohd Taufik, Dailami (2009)
Dragon fruit is a species of non seasoning fruit. This tree can produce fruit whole year and the fruit are harvest at anytime in the year. This fruit mostly consumed freshly. So the market for this fruit are limited and have limited period because of the fruit will turn bad after a few day of harvesting. To increase the economics of this fruit, product of this fruit should be varies where widen market are available. The product can be varies by producing powder of fruit juice where the potential of this type of product are large. This product can be keep for long time and it easy to market anywhere. The objective of this experiment is to produce dragon fruit powder using fresh fruit. By manipulating temperature and percentage of maltodextrin used to produce as much as possible of powder and retain the natural vitamin content. The powder should be fine particles and soft with bright red color and able to be keep for long period. The temperature (oC) used in this experiment are 150, 160, 170, 180 and 190and using maltodextrin by 5, 10, 15, 20 and 25 percent for every 200ml of dragon fruit juice. By using spray dryer, powder is produce for each temperatures and percentage of maltodextrins. The powder is then test on solubility, moisture content, dissolubility rate and vitamin C content. Result from this experiment find that the optimum temperature should be used for production of dragon fruit powder is 180oC by using 20% of maltodextrin. Powder produce using this parameter are fine and soft powder.-Author-